Mechanism of Residual Lumen Stenosis at the Side Branch Ostium After Final Kissing Balloon Inflation: A Volumetric Intracoronary Ultrasound Study of Coronary Bifurcation Lesions. (29th January 2016) - Yamawaki, Masahiro; Murasato, Yoshinobu; Kinoshita, Yoshihisa; Fujii, Kenichi; Fujino, Yoshihisa; Shinke, Toshiro; Takeda, Yoshihiro; Yamada, Shinichiro; Shimada, Yoshihisa; Tsukahara, Reiko; Muramatsu, Toshiya; Suzuki, Takahiko; et al.
Abstract : Objectives: To investigate the mechanisms of residual stenosis (RS) at side branch ostium (SBO) after final kissing balloon inflation (FKI) and clarify the impact of carina‐ and plaque‐shifts on RS. Background: Carina‐ and plaque‐shift induce SBO compromise. FKI is an effective technique to treat this complication; however, RS often persist, and are associated with restenosis at SBO. Methods: We performed serial volumetric analysis of 91 bifurcations in which crossover‐stenting with FKI and pre‐/post‐intravascular ultrasounds (IVUS) were completed in both branches. The plaque‐ and carina‐shifts were defined as an increase in the plaque‐volume and a decrease in the vessel‐volume at the SBO, respectively. RS at the SBO, defined as area stenosis >50% on IVUS, was identified in 19 lesions. Results: After FKI, the plaque volume‐ significantly increased at the SBO, with its reduction in the proximal main vessel (MV). However, at the SBO, the volumetric lumen change correlated with vessel change (ρ = 0.690, P < 0.001), but not plaque change (P = 0.390), suggesting that RS at SBO was more likely associated with inadequate vessel stretch, not plaque increase after FKI. Carina‐shift was more frequently found in cases with RS, compared to those without RS (37% vs. 11%, P = 0.013). Pre‐procedure IVUS findings to predict RS at SBO after FKI were negative‐remodeling at distal MV, plaque ‐burden at distal MV, and plaque‐burden at the SBO. Conclusions: Carina‐shift has a greater contribution to the formation of RS at SBO after FKI. The pre‐procedure IVUS provides helpful information for predicting the RS after FKI. (J Interven Cardiol 2016;29:188–196)